Modulation of Helicobacter pylori induced interleukin-8 synthesis in gastric epithelial cells mediated by cag PAI encoded VirD4 homologue. - Crabtree, J E (1999)
BACKGROUND: Strains of Helicobacter pylori carrying the virulence associated cag pathogenicity island (PAI) induce gastric epithelial synthesis of the chemokine interleukin-8 (IL-8), a neutrophil chemoattractant, and thereby a strong inflammatory response during chronic infection of the human gastric mucosa. Previous mutational analyses have shown that many genes in the cag PAI are needed to elicit IL-8 synthesis in gastric epithelial cells, and also that some genes are not involved. AIM: To test the possibility that certain genes in the cag PAI also downregulate (modulate) the inflammatory response elicited by cag+ H pylori infection. METHODS: Cells of L5F11, a derivative of the Kato-3 gastric epithelial cell line that carries an engineered IL-8 promoter-luciferase reporter gene fusion, were cocultured with H pylori strain 26695 or with an isogenic mutant in which most of the cag PAI ORF 10 gene, an Agrobacterium virD4 homologue, was deleted. Luciferase activity was measured to assess IL-8 gene transcription and secreted IL-8 was measured by enzyme linked immunosorbent assay to assess synthesis and release of IL-8 protein from gastric epithelial cells. RESULTS: Inactivation of ORF10 led to a 2.8-fold increase in IL-8 gene transcription and a 3.6-fold increase in IL-8 synthesis and secretion. CONCLUSIONS: The results suggest that this VirD4 homologue participates in the control of inflammation that H pylori infection elicits by downregulating (modulating) the strong induction of IL-8 synthesis mediated by other cag encoded proteins.